2017
DOI: 10.1093/gbe/evx118
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the Origins of the Negritos, First Sundaland People: Deep Divergence and Archaic Admixture

Abstract: Human presence in Southeast Asia dates back to at least 40,000 years ago, when the current islands formed a continental shelf called Sundaland. In the Philippine Islands, Peninsular Malaysia, and Andaman Islands, there exist indigenous groups collectively called Negritos whose ancestry can be traced to the “First Sundaland People.” To understand the relationship between these Negrito groups and their demographic histories, we generated genome-wide single nucleotide polymorphism data in the Philippine Negritos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 54 publications
4
53
3
Order By: Relevance
“…However, there are some studies that contradict this approach. The fossil record confirms that our modern humans were in the Philippines at least 40,000-50,000 years ago [3][4][5] , the genus Homo possibily 66,700 years ago 6,7 . Another finding is the presence in the archipelago of Negritos groups related to the first migrations of Homo sapiens outside Africa 4,8,9 .…”
supporting
confidence: 74%
“…However, there are some studies that contradict this approach. The fossil record confirms that our modern humans were in the Philippines at least 40,000-50,000 years ago [3][4][5] , the genus Homo possibily 66,700 years ago 6,7 . Another finding is the presence in the archipelago of Negritos groups related to the first migrations of Homo sapiens outside Africa 4,8,9 .…”
supporting
confidence: 74%
“…2), including many hunter-gatherer groups, generally correlates with the extent of their shared ancestry with the Australo-Papuan populations who first moved through the area (28,30). Intriguingly however, the Denisovan genomic content of Philippines hunter-gatherer groups is proportionally much higher (28,41). Initially, this pattern was attributed to dilution of the Denisovan signal in the Australo-Papuan ancestors after their separation from the Philippines groups, presumably by admixture with a population carrying no Denisovan DNA (28).…”
Section: Denisovan Dna Across Wallace's Linementioning
confidence: 99%
“…2). Curiously, however, long-isolated SEA hunter-gatherer groups, such as the Andaman Islanders and Malaysian Jehai, also show relatively low amounts of Denisovan ancestry (28,41). Given they are unlikely to have been impacted by Holocene farming groups, this would suggest that a much earlier phase of admixture with non-Denisovan containing AMH populations also took place.…”
Section: Denisovan Ancestry In Contemporary Amh Populationsmentioning
confidence: 99%
“…The isolation of Australo-Papuan populations in Sahul (the continent of New Guinea-Australia-Tasmania) around 50 ka 3 preserved their EH1 and Denisovan genomic content from dilution by admixture with later AMH populations lacking these signals, such as Holocene farming groups, which are likely responsible for the low hominid genomic signals seen in modern AMH populations across Asia and ISEA 14 ( Fig 1C). However, the lower than expected amounts of Denisovan ancestry in long-isolated SEA hunter-gatherer groups, such as the Andaman Islanders and Malaysian Jehai 10,15 , potentially indicates an early phase of admixture with non-Denisovan containing AMH populations. While some genetic studies have also reported a unique Denisovanlike introgression signal in East Asian populations 12 , the finding of the ancestral EH1 genomic contribution potentially explains both this, and the slightly higher Neandertal genomic ancestry described in these populations 13 .…”
mentioning
confidence: 90%
“…1), including many hunter-gatherer groups, correlates with the extent of their shared ancestry with the ancestral Australo-Papuan populations who first moved through the area 10,11 . Intriguingly however, relatively higher Denisovan proportions are detected in Philippines hunter-gatherer groups 10,15 , apparently recording a further independent introgression with Denisovans, following their separation from the ancestors of Australo-Papuan populations 15 (as depicted in Fig 1B). This raises the distinct possibility that the introgression events recorded in the Philippines populations took place east of Wallace's Line, and if so, that perhaps multiple populations of Denisovans were present on other islands in the area.…”
mentioning
confidence: 92%